On optical solitons for the nonlinear fractional twin-core couplers with Kerr law nonlinearity - Luo, Renfei; Rezazadeh, Hadi; İnç, Mustafa; Shallal, Muhannad A.; Mirhosseini-Alizamini, Seyed Mehdi; Akinlar, Mehmet Ali (Springer, 2022)
This study presents new soliton solutions for the nonlinear fractional twin-core couplers with Kerr law nonlinearity by employing the modified extended tanh method with Riccati equation. The solutions are expressed in terms of some elementary functions including rational, trigonometric and hyperbolic types. Graphical demonstrations of the simulations are provided.
Keywords: The modified extended tanh method with Riccati equation; Nonlinear fractional twin-core couplers with Kerr law nonlinearity; Soliton solutions; Atangana-Baleanu fractional derivative